Critiquing a Critique. - Miller, Keith W. (Science & Engineering Ethics, 2008)
The author comments on James Stieb's articles "A Critique of Positive Responsibility of Computing." He contends that Stieb's claims are overstated. The author stresses that, contrary to the claim of Stieb that author Don Gotterbarn is holding computer professionals responsible for an undisclosed list of undesirable events, Gotterbarn is only encouraging computer professionals to take responsibility for their work. He says Stieb's assertion that the primary goal of professionalism should be competent creation is in the code of ethics Stieb is criticizing.